The Social Effect of the IMF Policies Post Arab-Spring in the Middle East - Nafie, Noha (AUC Knowledge Fountain, 2021)
This study discusses how International Financial Institutions (IFIs), primarily the International Monetary Fund (IMF), have incorporated the social dimension when designing their reform programs in the Middle East. This research explores three case studies of IMF programs in Tunisia, Jordan and Egypt, and examines how the process of designing and implementing social protection programs has changed after the Arab Spring. The Egyptian case study provides an in- depth analysis of the design of Takaful and Karama in particular and its implementation. Moreover, it provides a future outlook on the protection programs in Egypt with implications for the wider MENA region. This study adopts a case study approach using qualitative tools such as content analysis of the three countries mentioned above in addition to in-depth, semi-structured interviews with regional experts. The interviewees for this research included IFI officials, government representatives, academics and researchers in the field of social policies as well as beneficiaries from the Egyptian Takaful and Karama programs. The findings of the research denotes that IMF’s inclusion of the social protection aspect is evident post 2011 Arab Spring. The study provides an insights governments’ efforts towards the social protection programs and looks at the future outlook for Middle East state-run social protection programs. Among the main findings was that the paradigm shift of the IMF reflected a change in rhetoric with minimal on the ground changes, which shoes how the IMF’s role in the region regarding social protection programs needs to be further examined, especially in the policy recommendations. The region is in the early stages regarding the design of the protection programs and in the future should widen the scope to focus on inequality issues rather than addressing the reduction of poverty.